EXTH-38. ENGINEERED EXOSOMES FOR THERAPEUTIC GENE DELIVERY IN BRAIN TUMORS. (11th November 2019) - McDonald, Malcolm; Hasan, Irtiza; Adachi, Satoshi; Gumin, Joy; Ledbetter, Daniel; Daou, Marc; Gopakumar, Sricharan; Momin, Eric; Long, Lihong; Phillips, Lynette; Parker-Kerrigan, Brittany; Hossain, Anwar; et al.
Abstract: The poor outcome of patients with glioblastoma (GBM) is at least partly due to the inability to deliver therapeutic agents to the tumor. We have shown that exosomes, naturally occurring nano-size extracellular vesicles, are capable of delivering antiglioma microRNAs (MiRs) to brain tumors (Lang, FM et al. Neuro Oncol, 2018;20(3):380–390). However, our studies suggested that there is significant opportunity to increase packaging efficiency and delivery specificity of exosomes. To this end, we engineered exosomes to express specific viral proteins (called eExos) in order to enhance packaging and delivery capabilities of antiglioma genes. These eExos are created by transfecting HEK 293 cells with plasmids containing viral proteins and a plasmid of the therapeutic gene. After 72 hrs, differential ultracentrifugation was used to isolate the exosomes. To test the efficacy of these novel eExos, we transfected them with a plasmid containing Cre recombinase (as the therapeutic gene), and treated U87 cells harboring a dsRed/eGFP Cre recombinase/LoxP site (U87dsR/GFP). In in vitro studies, treatment of U87dsR/GFP with a single dose of eExos resulted in 82% conversion rate of cells from red to green, compared to control exosomes (< 18% green cells). In in vivo studies, a single intratumoral injection of eExos into mice harboring 7-day old intracranial U87dsR/GFP gliomas, resulted in significant increases in green cells compared to control exosomes when tumors were harvested at day 10. Mechanistic studies employing florescent microscopy demonstrate that in contrast to natural exosomes, eExos deliver their cargo to the nucleus rather than to lysosomes, avoiding degradation of the delivered agent and facilitating expression of the plasmid. We conclude that eExos, engineered to contain specific viral proteins, are capable of packaging and delivering antiglioma genes more effectively than natural exosomes and may overcome the current inability to deliver biological therapeutic agents to brain tumors.